Comparative analysis of anthropometric indices with serum uric acid in Iranian healthy population. Issue 2 (16th January 2022) - Soori, Hamid; Rezapoor, Parinaz; Najafimehr, Hadis; Alirezaei, Toktam; Irilouzadian, Rana
Abstract: Background: The relationship between elevated serum uric acid (SUA) levels and hypertension, metabolic syndrome and cardiovascular disease has been established. In this study, the relation of SUA levels to anthropometric indices, blood cell count and lipid profile was examined. Methods: Anthropometric parameters including body‐mass index, waist circumference, waist to height ratio, waist to hip ratio, waist to pelvic ratio, neck circumference (NC), body fat mass (BFM), basal metabolic rate (BMR), visceral fat level (VFL) and percent body fat (PBF), along with complete blood cell count, lipid profile and SUA were obtained from 2921 young and middle‐aged Iranian healthy subjects. To assess the normality of data, the Kolmogorov–Smirnov test was used. Mann‐Whitney, Kruskal‐Wallis, Chi‐square and Spearman correlation tests were used for evaluating the association between variables. Simple and multiple regression analyses were also performed. Results: The results of data analysis showed all studied factors were correlated with SUA level except VFL, BFM, and platelet‐to‐lymphocyte ratio. The highest correlation was with NC, BMR, hematocrits (HCT) and triglycerides (TG). The backward method revealed that TG, LDL, HDL, neutrophil, lymphocyte, platelet, HCT, BMR and skinfold fat thickness were factors related to SUA. Conclusions: According to the finding of this study, SUA level is related to anthropometric indices, lipid profile and neutrophil to lymphocyte ratio in healthy population. SUA measurement might be advisable to identify those at increased risk of health problems whom might benefit from further evaluation. Abstract : Serum uric acid level is correlated with anthropometric indices, lipid profile and complete blood count parameters.